Carry on, Mr. Bowditch - Latham, Jean Lee.; Cosgrave, John O'Hara, II, 1908-1968 (Boston : Houghton Mifflin, 1955)
After finding a way to teach the ship's crew members to understand navigation, Nat, a self-taught mathematician and astronomer in eighteenth-century Salem, Massachusetts, writes down his explanations and compiles them into "The American Practical Navigator," also known as the "Sailors' Bible."
Good-luck spell -- Privateers -- Word from the pilgrim -- "Boys don't blubber" -- Voice in the night -- "Sail by ash breeze!" -- Almanac -- "Lock, stock, and bookkeeper" -- Anchor to windward -- Freedom -- What next? -- Down to the sea -- Discovery -- Nineteen guns -- "Sail Ho-O-O-O-O!" -- Simple matter of mathematics -- Lunars and moonlight -- Astrea to the rescue -- Strange sailing orders -- Book sailing -- "Sealing is safer" -- Science and sumatra -- Captain Bowditch commanding -- Man against the fog
Middle School
Accelerated Reader
Keywords: Bowditch, Nathaniel, -- 1773-1838 -- Juvenile fiction; Inventors -- United States -- Biography -- Juvenile literature; Sailors -- United States -- Biography; Nautical charts -- History; Aids to navigation -- Juvenile literature; Seafaring life -- Juvenile literature; Navigation -- Juvenile fiction; Salem (Mass.) -- History -- 18th century -- Fiction; Biographical fiction -- Juvenile; Historical fiction; Biography; Fiction; History; Juvenile works; Biographical fiction; Historical fiction